Penentuan Aktivitas Antioksidan Mirisetin, Quersetin Dan Kaempferol Berdasarkan Metode Semiempiris Austin Model (AM 1) - Azuxetullatif, Azuxetullatif (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Research has been conducted on the determination of antioxidant activity using the parameters of Bond Dissociation Enthalpy (BDE), Single Electron Transfer-Proton Transfer (SET-PT), Proton Affinity (PA), and Electron Transfer Enthalpy (ETE) of myricetin, quercetin, and kaempferol compounds. Furthermore, through the geometric stages using the AM1 semi-empirical method. The results obtained showed that myricetin compounds have better antioxidant activity compared to quercetin and kaempferol compounds by considering the results of high BDE values, low SET-PT, high PA, and low ETE.